Design of 3 DOF hexapod leg movement using inverse kinematics: bridging gaps in multilegged robot kinematics literature - Suwoyo, Heru; Taufikurohman, Nur Aziz; Tian, Yingzhong; Burhanudin, Achmad (Universitas Mercu Buana, 2025)
Designing the motion of a hexapod robot with 3 Degrees of Freedom (DOF) using the Inverse Kinematics method allows the robot to move by adjusting the angles of its leg joints according to the desired position and direction. This research involves the geometric and structural design of the hexapod robot and the development of an Inverse Kinematics algorithm to calculate the leg joint angles based on the target pose. The study uses the Inverse Kinematics method to design a hexapod robot for movement with 3 DOF. The testing results show an average Inverse Kinematics error of 1.56 mm on the X-axis, 0.88 mm on the Y-axis, and 0.78 mm on the Z-axis. During the forward and backward movement tests covering a distance of 100 cm, the average error was 2.58 cm and 12.38 cm, respectively. For the rotation tests, the average error was 3.6° for a 90° rotation to the right, 3° for a 90° rotation to the left, 13.2° for a 180° rotation to the right, and 3.8° for a 180° rotation to the left. The results indicate that the design of the 3DOF hexapod robot using the Inverse Kinematics method provides a sufficient level of accuracy in controlling movements along the X, Y, and Z axes. Despite some errors, the robot is capable of moving fairly accurately during forward, backward, and rotational movements.